Pendidikan Kesehatan Menuju Kelurahan Sehat di Kelurahan Lambung Bukit, Pauh, Kota Padang - Aldina Ayunda Insani; Rafika Oktova; Erda Mutiara Halida; Miranie Safaringga; Fitrayeni Fitrayeni; Feni Andriani; Heni Fitria; Lidya Riniati; Malika Qohhareli Swanda; Fharyn Mayyurid; Raisa Fajriati; Nadia Shabira Amima; Syartika Dharma; Jelsita Nova (Warta Pengabdian Andalas, 2023)
Community service activities related to community midwifery care aim to explore existing health and midwifery problems, find solutions with the community, and make promotive and preventive efforts for the problems found. The method started with interviews using questionnaire instruments with the people in Kampung Pinang, Lambung Bukit Village, Pauh District, Padang City. The next step was holding a Village Community Consultation (MMD) and intervene based on the results of the MMD decision. The activity resulted in 70% of people having the habit of disposing of waste by burning it, 40% disposing of wastewater into ditches/rivers, and 74% of couples of childbearing age not using family planning (KB) contraception. Health education about personal hygiene, environmental cleanliness, waste processing methods, and family planning contraceptives were provided. The method used was counselling and using leaflet media for further education. There needs to be cooperation in all sectors, assistance from the environmental cleanliness, health and midwifery sectors, and direct involvement from community leaders. The existence of a cooperation schedule and evaluation of activities will enable the continued application of the education provided in a better direction to improve the level of health and an optimal environment.